Optimalisasi Kemampuan Identifikasi Masalah Penelitian Mahasiswa PAI UIN Salatiga Melalui Technical Guidance Penyusunan Latar Belakang Skripsi: Optimizing the Ability to Identify Research Problems of Islamic Religious Education Students at UIN Salatiga through Technical Guidance for Compiling Thesis Backgrounds - Muhammad Yoggi Aqsal Darmawan (Information Technology and Science (ITScience), 2026)
This community service activity aims to enhance the ability of Islamic Religious Education (PAI) students at the State Islamic University (UIN) Salatiga to identify research problems, an important prerequisite for thesis writing. This is based on their low initial ability to formulate issues and theories, write systematically, and identify research gaps in the background, which creates an urgent need for structured technical support to bridge the gap between sharp problem identification and the systematic preparation of a logical, structured thesis background. The realization of the activity was carried out through Technical Guidance for one hour and thirty minutes, involving 21 final year PAI students at UIN Salatiga, with the focus of the material on variable analysis, techniques for dissecting the state of the art, and strategies for compiling a logical flow that culminates in the formulation of a strong research gap. The results of the activity showed a significant improvement in the quality of the participants' thesis background draft, with students identifying research problems more specifically and logically, and supporting them with adequate arguments. This community service activity concludes that Technical Guidance in thesis background preparation is a highly effective and relevant method for improving PAI students' ability to identify research problems, thereby directly expediting the completion of their studies at UIN Salatiga.